280 Quality grading using color and electrical conductivity of beef. (5th December 2019) - Richardson, C Reed; Ramkumar, Mala S
Abstract: Four sources of beef were used to determine if the degree of variance in color (Hunter LH) and electrical conductivity (EC) measures correlate to quality grade. It also tested the reliability of the Varian spectrophotometer machine for color scores on beef. Source 1 (S1) samples varied in cuts that were frozen then thawed. S2 – S4 were delivered whole and cut into 16 individual, 1-inch thick samples. Source 2 (S2) was a whole boneless ribeye and choice grade; Source 3 (S3) was a whole strip loin, Wagyu breed and prime grade; Source 4 (S4) was a whole strip loin, Akaushi breed and prime grade. All color measurements (n = 48) were taken on raw samples. EC (n = 48) was measured in microsiemens (μS) for 120s with sampling rate of two measures per s. An emulsified meat slurry solution was placed into a 3in wide silicon vessel with copper electrodes attached to both sides, and placed into plastic container connected to a digital multimeter. Analysis of variance (ANOVA) was used for data analysis on color & EC replications and total color & EC means and performed across S1 then S2 – S4. Color results across color mean replications for individual samples were non-significant (P > 0.05, 95% confidence level). Source color means for S1=33.6873, S2=55.4319, S3=47.8122 & S4=53.5633. S1 had the lowest LH mean compared to S2-S4 and presumed to be a result of myoglobin state. These data indicate reliability of the Varian color machine as method for scoring steaks. EC results showed prime grades S3 and S4 had lower scores compared to S1 and S2 with EC means of S1=24.8043, S2=63.5294, S3=17.0451 & S4=18.9656. S3 & S4 both had significant correlations (P < 0.05) between EC and color scores indicating EC and color correlations can be useful in quality grading of beef.